Analysis of Education Financing of Non-Formal Educational Institutions: a Case Study on Course Educational Institutions - Sukoco, Agus; Budi, Gagah Agung Sulistyo; Latif, Imam Nazarudin; Bon, Abdul Talib Bin (Journal of Nonformal Education, 2024)
Non-formal educational institutions such as course institutions are educational paths outside of formal education that can be carried out in a structured and tiered manner. The purpose of this study is to identify effective partnership strategies in raising funds for education financing in course institutions, as well as to develop the quality and relevance of non-formal education to the needs of the world of work. The literature review will encompass various sources, including peer-reviewed journal articles, government reports, and case studies that discuss the financing mechanisms of non-formal educational institutions. Key areas of focus will include the identification of effective partnership strategies, fund management practices, and quality development initiatives within course institutions. By synthesizing findings from multiple studies, this research aims to provide a holistic understanding of how course institutions can effectively secure funding and improve educational outcomes. The findings of this study are related to the Partnership Strategy: More course institutions are working with the government and the private sector to raise funds. These partnerships help improve the accessibility and quality of education. Fund Management: Effective fund management through appropriate allocation of aspects of the teaching and learning process, as well as the use of technology to increase efficiency. Quality Development: Improving the quality of education is carried out by prioritizing the allocation of aspects of the teaching and learning process, as well as teacher and staff training. The conclusion of this study is that course institutions can increase the effectiveness and relevance of non-formal education by developing effective partnership strategies, appropriate fund management, and quality development of education that focuses on the teaching and learning process. This research adds value by providing concrete examples of how course institutions can develop partnership and fund management strategies to improve the quality and relevance of non-formal education. In addition, this study also emphasizes the importance of focusing on the teaching and learning process in improving the quality of education.